The Effect of Avoidant Attachment Style on Marital Satisfaction with the Mediating Role of Fear of Intimacy - SeyedEbrahimi, Seyed AliAsghar; Hojjati Hamedani, Ata (KMAN Counseling & Psychology Nexus, 2024)
This study aimed to examine the effect of avoidant attachment style on marital satisfaction, with fear of intimacy as a mediating variable in a sample of married individuals in Tehran. A descriptive correlational design was employed with a sample of 400 married adults selected based on Krejcie and Morgan's sample size table. Participants were recruited from various community centers across Tehran using convenience sampling. Standardized instruments were used to measure avoidant attachment (Experiences in Close Relationships-Revised), fear of intimacy (Fear of Intimacy Scale), and marital satisfaction (ENRICH Marital Satisfaction Scale). Data were analyzed using SPSS-27 for descriptive and correlational statistics, and AMOS-21 for structural equation modeling (SEM). Model fit was assessed using χ², RMSEA, CFI, TLI, and other relevant indices. Pearson correlation analysis showed that avoidant attachment was positively correlated with fear of intimacy (r = .62, p < .001) and negatively correlated with marital satisfaction (r = –.53, p < .001). Fear of intimacy was also negatively associated with marital satisfaction (r = –.47, p < .001). SEM results confirmed a good model fit (χ²/df = 2.01, RMSEA = .051, CFI = .96, TLI = .95). Avoidant attachment significantly predicted fear of intimacy (B = 0.78, β = .62, p < .001) and marital satisfaction (B = –0.46, β = –.38, p < .001). Fear of intimacy also significantly predicted marital satisfaction (B = –0.39, β = –.34, p < .001), and the indirect effect of avoidant attachment on marital satisfaction via fear of intimacy was significant (B = –0.30, β = –.21, p < .001). These findings suggest that avoidant attachment style diminishes marital satisfaction both directly and indirectly through increased fear of intimacy. Addressing intimacy-related anxieties in therapy may improve relationship outcomes for avoidantly attached individuals.